All Quiet on the Western Front (All Quiet on the Western Front/The Road Back #1) - Erich Maria Remarque (New York Random House Trade Paperbacks, 2013)
One by one the boys begin to fall... In 1914 a room full of German schoolboys, fresh-faced and idealistic, are goaded by their schoolmaster to troop off to the 'glorious war'. With the fire and patriotism of youth they sign up. What follows is the moving story of a young 'unknown soldier' experiencing the horror and disillusionment of life in the trenches.
Keywords: Classics; War novel; Fiction; Historical fiction